The dynamic influence of interactive feedback on elevating EFL students writing skills - Masrul Masrul; Bayu Hendro Wicaksono; Sri Yuliani; Santi Erliana; Ummi Rasyidah (Universitas Syiah Kuala, 2024)
This study investigates the effect of interactional feedback on students writing skills. One hundred participants enrolled in an intermediate EFL course at the State University of Malang, Indonesia, were recruited for this research. The quantitative method was employed for data analysis. The primary data analysis method used was the ANCOVA test, followed by the Wilcoxon and Mann-Whitney tests. The results reveal that the dependent variables in the experimental group exhibited higher means compared to the control group. The ANCOVA test show that the dependent variables (writing length, accuracy, and effectiveness) were significantly affected by the addition of feedback (p = 0.000). However, no significant differences were found between the experimental and control groups regarding accuracy (p = 0.425) and writing length variables (p = 0.731). As a result, interactional feedback significantly impacted EFL students writing ability. This result highlights the need for thorough planning and preparation, including preparing ESL/EFL students through explicit instruction prior to peer review, to ensure that learners interactional feedback is useful. The findings suggest that EFL teachers should carefully select feedback styles that align with the intended purpose of providing feedback. For instance, more specific feedback options may prove more effective in assisting students in revising and improving their written assignments. Finally, this study provides valuable recommendations for further research in this field.